Sonographic features of patients with ocular trauma at the University of Benin Teaching Hospital, Benin-City - Sally Ozougwu; Ademola Adeyekun; Juliet Ese-Onakhewor; Elo Efe-Aluta (Annals of Health Research, 2018)
Background: The human eye is vulnerable to various external injuries. This is in spite of the seemingly adequate protection offered by the bony orbit. Ultrasound, as a non-invasive and safe imaging modality, is very useful in evaluating the orbit as the globe provides a perfect acoustic window. There is a need for an update on the sonographic patterns of ocular trauma in Nigeria. Objective: To sonographically assess the features of ocular trauma at the University of Benin Teaching Hospital. Methods: Eighty patients with ocular injuries were studied over an 8-month period. After detailed history taking, using a closed eye technique, each patient was scanned with a 5-12MHz linear array probe of a SONOACE X4 Machine. Results: The 18-35 years age group was most affected and the right eye was more frequently involved. The most common sources of injury were intraocular foreign bodies (26; 32.5%), assault (20; 25%) and road traffic accidents (18; 22.50%). Mechanical injuries were more common, comprising 44 (56.4%) cases of blunt trauma and 34 (43.6%) cases of penetrating trauma. The most common sonographic findings included vitreous haemorrhage, intraocular foreign bodies and retinal detachment. Conclusion: Posterior chamber findings (vitreous haemorrhage and retinal detachment) were more frequent than anterior chamber findings in ocular trauma.